Usefulness of urinary tubule injury markers for predicting progression of renal dysfunction in patients with type 2 diabetes and albuminuria: The Fukuoka Diabetes Registry. (April 2022) - Ide, Hitoshi; Iwase, Masanori; Ohkuma, Toshiaki; Fujii, Hiroki; Komorita, Yuji; Oku, Yutaro; Higashi, Taiki; Yoshinari, Masahito; Nakamura, Udai; Kitazono, Takanari
Abstract: Aims: We prospectively investigated the association of urinary tubule injury markers with estimated glomerular filtration rate (eGFR) decline in Japanese patients with type 2 diabetes. Methods: Urinary kidney injury molecule 1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), liver-type fatty-acid-binding protein (L-FABP), and urinary albumin-to creatinine ratio (UACR) were measured in 2, 685 participants with type 2 diabetes. Renal outcomes were ≥ 30% decline in eGFR from the baseline and annual eGFR decline for 5 years. Results: In normoalbuminuric participants, no tubular markers were associated with ≥ 30% decline in eGFR or annual eGFR changes. In those with UACR ≥ 30 mg/gCr, hazard ratios for ≥ 30% eGFR decline were 1.37 (95% confident interval (CI) 1.07–1.75) for urinary KIM-1 (>1.5 µg/gCr), 1.46 (95% CI 1.13–1.66) for urinary NGAL (>16.4 µg/gCr), and 1.26 (95% CI 0.94–1.66) for urinary L-FABP (>12.5 µg/gCr), 2.61 (95% CI 1.64–4.17) for the combination of 3 tubular markers above the cutoff after multivariable adjustments including UACR and eGFR. Conclusions: The current study demonstrated that urinary tubule injury markers and their combination were significant predictors for the future eGFR decline in those with type 2 diabetes and albuminuria independently of UACR and eGFR. Urinary tubular markers may be useful to identify high-risk patients with albuminuria.